2020
DOI: 10.26444/aaem/110958
|View full text |Cite
|
Sign up to set email alerts
|

Coping strategies observed in women with rheumatoid arthritis

Abstract: When faced with a chronic disease such as rheumatoid arthritis, the patient attempts to cope with the stressful situation by applying coping strategies. The main aim of rheumatoid treatment is not only improving health but also increasing the quality of life. The research objective was to determine the relationship among socio-demographic factors, duration of the disease and its associated ailments, attitude to the disease, self-assessment of one's knowledge of RA, and the application of coping strategies in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
(30 reference statements)
1
11
0
2
Order By: Relevance
“… 11 In index study, denial had greater scores followed by internalization coping. In line with recent study, 12 we also found association of coping with age, duration of illness, disease severity indicators, as anger coping was less reported in older patients, greater externalization coping was used in earlier course of RA, and more use of internalization coping was seen with greater disease severity. In index study, internalization coping (to increase the risk) and externalization coping (to reduce the risk) were significant predictors for psychiatric disorders.…”
Section: Discussionsupporting
confidence: 92%
“… 11 In index study, denial had greater scores followed by internalization coping. In line with recent study, 12 we also found association of coping with age, duration of illness, disease severity indicators, as anger coping was less reported in older patients, greater externalization coping was used in earlier course of RA, and more use of internalization coping was seen with greater disease severity. In index study, internalization coping (to increase the risk) and externalization coping (to reduce the risk) were significant predictors for psychiatric disorders.…”
Section: Discussionsupporting
confidence: 92%
“…This study is limited by the fact that all participants were Afro-Caribbean, and therefore, our findings may not be inclusive of the views of those of other ethnicities and cultures. In addition, the majority of our study sample may be categorised as having moderate to high socioeconomic status, 67 this profile has been reported to foster adaptive coping strategies, 68 69 including higher levels of pain acceptance and resilience. 70 71 We assume that this was no major issue, since the aim of this study was to gain in-depth insights of the personal adaptive coping strategies employed by individuals affected by long-term chikungunya disease.…”
Section: Discussionmentioning
confidence: 99%
“…Several benefits have been reported in relation to support, both in people with RA and in other conditions, such as different types of support affecting aspects of mental well-being of people with physical disabilities (17). Furthermore, support facilitates self-management behaviour (18) and health behaviours such as physical activity (20,21), and emotional support in particular is a well-used coping strategy in RA (19). Because the question our patients were asked consisted of emotional and practical support jointly, no conclusions can be drawn from our results regarding emotional support exclusively.…”
Section: Discussionmentioning
confidence: 99%
“…Support is often referred to as types of instrumental, emotional, or informational resources provided by the social environment (16). These various types of support are associated with different aspects of mental well-being (17) as well as self-management (18), coping (19), and health behaviours (20,21). Significant others who provide encouragement and motivation improve the likelihood that people with chronic diseases will continue working (22).…”
mentioning
confidence: 99%